“NECESIDAD DE REGULAR LA APLICACIÓN DEL ARTÍCULO 464 NUMERAL 5 DEL CÓDIGO ORGÁNICO INTEGRAL PENAL A FIN DE EVITAR AFECTAR LA PRESUNCIÓN DE INOCENCIA, EL PRINCIPIO DE EFICACIA PROBATORIA Y GARANTIZAR EL DEBIDO PROCESO EN LA OBTENCIÓN DE LA PRUEBA”. - RIVERA JIMÉNEZ, CHRISTIAN DANIEL (2021)
The present degree thesis is entitled: “Need to regulate the application of article 464 numeral 5 of the Comprehensive Organic Criminal Code in order to avoid affecting the presumption of innocence, the principle of evidentiary efficacy and guarantee due process in obtaining the proof ”, and the need for its execution arises due to the analysis of article 464 numeral 5 of the Comprehensive Organic Criminal Code, which does not detail a correct application by the Civil Traffic Agent to inform and give the driver the option of being responsible for choose which test you want to take to verify drunkenness or intoxication, taking into account that the Civil Traffic Agent is obliged to tell the driver what each of these tests consists of and emphasize the legal consequences and the possible penalty that he would confront by refusing to carry out the tests to verify the degree of intoxication or intoxication due to the effect of cataloged substances s subject to control. In the development of the thesis, materials and methods were applied to develop this legal research, for which we proceeded to conduct interviews and surveys with legal professionals, results that served to propose a project of legal reform to the Comprehensive Organic Penal Code and the Regulation of Application of the Organic Law of Land Transport, Traffic and Road Safety in article 245, incorporating rules that determine the Civil Traffic Agent to inform the driver about the legal consequences and the possible penalty that he would face if he refused to carry out the examinations of verification, recording the actions recorded on audio and video, thereby avoiding affecting the presumption of innocence, the principle of evidentiary efficacy and guaranteeing due process in obtaining evidence.